THE IMPORTANCE OF THE CONSERVATION/PRESERVATION WORKS: A CHALLENGE TOWARDS THE FUTURE OF NATIONAL HERITAGE - Muhamad, Asyaari (PLANNING MALAYSIA, 2018)
This article discusses the importance of archaeology in the conservation and restoration works in Malaysia. Even though the development of archaeology in the nation is approximately 200 years, it is still considered a new subject. Even so, more than 50 research projects on the archaeological conservation of buildings and historical sites have been completed in this nation. Some of the archaeological conservation projects completed include Kota Kuala Kedah, the candi of Lembah Bujang, Fort Cornwallis, Suffolk House, High Courts, and Shop Houses of (Lebuh Acheh) in Pulau Pinang, Muzium Matang in Pasir Salak, Balai Budaya in Kuala Lumpur, Kota Lukut in Negeri Sembilan, Kota Melawati and Istana Bandar in Selangor, Bangunan Onn Jaafar in Johor and Fort Megarittha in Sarawak. These archaeological conservation projects had varying success. Successful in this context is when a site is uncovered with carefully preserved and restored archaeological finds and the reconstruction of certain structures whereas unsuccessful is when all the archaeological finds are disregarded or even destroyed. Therefore, this article attempts to uncover several factors about the importance of archaeological activities in the conservation or restoration of buildings and historical sites. Among that being suggested is that all historical buildings or sites that have to preserved and conserved should first be investigated archaeologically, all archaeological finds should be restored, and reconstructed in order to preserve the specific authenticity of the historical building or site, some funds should be set aside for these activities, and that it should be undertaken by an archaeologist who is experienced and trained in this field.